Nosocomial Infection Following Severe Traumatic Injury in Children. Issue 5 (May 2020) - Sribnick, Eric A.; Hensley, Josey; Moore-Clingenpeel, Melissa; Muszynski, Jennifer A.; Thakkar, Rajan K.; Hall, Mark W.
Abstract : Objectives: Nosocomial infection is a common source of morbidity in critically injured children including those with traumatic brain injury. Risk factors for nosocomial infection in this population, however, are poorly understood. We hypothesized that critically ill pediatric trauma patients with traumatic brain injury would demonstrate higher rates of nosocomial infection than those without traumatic brain injury. Design: Retrospective case-control study. Setting: PICU, single institution. Patients: Patients under 18 years old who were admitted to the PICU for at least 48 hours following a traumatic injury were included. Patients were admitted between September 2008 and December 2015. Patients with the following injury types were excluded: thermal injury, drowning, hanging/strangulation, acute hypoxic ischemic encephalopathy, or nonaccidental trauma. Data collected included demographics, injury information, hospital and PICU length of stay, vital signs, laboratory data, insertion and removal dates for invasive devices, surgeries performed, transfusions of blood products, and microbiology culture results. Initial Pediatric Risk of Mortality III and Pediatric Logistic Organ Dysfunction-2 scores were determined. Patients were classified as having: 1) an isolated traumatic brain injury, 2) a traumatic injury without traumatic brain injury, or 3) polytrauma with traumatic brain injury. Interventions: None. Measurements and Main Results: Two hundred three patients were included in the analyses, and 27 patients developed a nosocomial infection. Patients with polytrauma with traumatic brain injury demonstrated a significantly higher infection rate (30%) than patients with isolated traumatic brain injury (6%) or traumatic injury without traumatic brain injury (9%) ( p < 0.001). This increased rate of nosocomial infection was noted on univariate analysis, on multivariable analysis, and after adjusting for other risk factors. Conclusions: In this single-center, retrospective analysis of critically ill pediatric trauma patients, nosocomial infections were more frequently observed in patients admitted following polytrauma with traumatic brain injury than in patients with isolated traumatic brain injury or trauma without traumatic brain injury.